Development of articulate storyline learning media integrated with religious values for sexual education in elementary school children - Indriani, Fitri; Aini, Nur (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
The escalating prevalence of violent behavior, sexual deviations, and juvenile delinquency within educational settings underscores the urgency for effective intervention strategies. This study endeavors to address this pressing issue by designing religious, value-oriented, narrative-driven educational media aimed at imparting sexual education to elementary school children. Employing a Research and Development (R&D) approach grounded in the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research team meticulously crafted and refined the learning materials. Validation of the developed products involved rigorous scrutiny by a diverse panel of experts, including media specialists, materials experts, pedagogical experts, linguists, educators, and students. This comprehensive validation process integrated both qualitative and quantitative analyses to ensure the robustness and efficacy of the educational resources. Evaluation of the products yielded promising results, with expert validators assigning an overall score of 85, denoting a "Very Good" quality assessment. Furthermore, assessments from teachers and students echoed this sentiment, with scores of 94.3 and 85.1, respectively, both falling within the "Very Good" category. The cumulative data score, totaling 264.4 with an average of 88.1, further validates the effectiveness and utility of the developed learning materials. In conclusion, the findings of this study highlight the viability and effectiveness of religious value-based narrative learning media in delivering sexual education to elementary school children. These findings not only contribute to addressing the pressing societal concern of juvenile delinquency but also offer tangible educational resources for instructional use in diverse educational settings.